ADVANCING MOTOR EFFICIENCY: ENHANCING INDUCTION MOTOR FUNCTIONALITY WITH CIRCULAR FLUX TRAJECTORIES IN DIRECT TORQUE CONTROL - Carter , Emily (Ayden Journal of Agriculture and Allied Studies, 2024)
Induction machines have long held a pivotal role as robust and reliable workhorses within the industrial landscape, making them the prime choice for motor-driven applications. The prevalence of induction motor control drives in global markets underscores their dominance. This paper delves into the intricacies of controlling induction motor drives powered by voltage source inverters instead of the traditional three-phase main source. This approach offers enhanced control over both electromagnetic torque and stator flux linkage directly and seamlessly. The voltage source inverter facilitates the generation of precisely controlled PWM signals with amplitude governed by the DC link, which are then utilized to synthesize phase voltages. The focal point of this study is the analysis of the mathematical model of AC motors in the stator coordinate system. This framework serves as the basis for exerting control over the motor's flux linkage and torque. By adopting this methodology, the necessity for convoluted transformations and intricate calculations, such as vector rotation transformations, is obviated. Consequently, signal processing is simplified, and the control signals employed enable the observer to discern the physical processes of the AC motor with directness and clarity.